Transregnal kingship in the thirteenth century - Peltzer, Jörg; Vincent, Nicholas (Proceedings of the British Academy Series:Themed Volumes of Essays in the Humanities and Social Sciences, 2025)
Transregnal Kingship in the Thirteenth Century explores a wide-spread European phenomenon: rulership over multiple kingdoms, or a kingdom in combination with major non-royal lordships elsewhere